Respostas

  • Ind
  • Ambicioso
2014-02-17T16:03:08-03:00
A2 = A1 + R 
A3 = A1 + 2 R 
A4 = A1 + 3R 
A5 = A1 + 4R 

I) A1 + A2 + A3 = 12 >>> A1 + (A1 + R) + (A1 + 2R) = 12 >>> 3.A1 + 3.R = 12 
Simplificando por 3, temos : A1 + R = 4 

II) A3 + A4 + A5 = 30 
(A1 + 2R) + (A1 + 3R) + (A1 +4R) = 30 >>> 3.A1 +9R = 30 , Simplificando por 3, temos: A1 + 3R = 10 

 \left \{ {{A1 + R = 4} \atop {A1 + 3R = 10 }} \right.

multiplicando a I por - 1 >>> - A1 - R = - 4

 \left \{ {{- A1 - R = - 4} \atop {A1 + 3R = 10 }} \right.

2R = 6
R = 3 

A1 + R = 4 
A1 + 3 = 4 
A1 = 1 

PA ( 1, 4 , 7 , 10, 13, 16, ...)